Recommendations for Appropriate Design for Handling Landslides on the Slopes of the Balai River (Sei Balai), Batubara Regency - Semangat Marudut Tua Debataraja; Agustinus Purna Irawan; Aazokhi Waruwu (International Journal Labs, 2024)
Sei Balai River, precisely in Nibung Hangus/Tanjung Tiram District, Batu Bara Regency, is one of the rivers in the Bah Bolon River Area (WS). Sei Balai River has experienced flooding several times and caused landslides on the riverbanks. One of the most critical locations is in Lima Beras Village, Nibung Hangus/Tanjung Tiram District, Batu Bara Regency, which has damaged the riverbanks which are feared that if not handled early, it may result in the breaking of community access roads in the mobilization and demobilization of agricultural and plantation products in the village. Based on the results of the geotechnical investigation, it was concluded that the Bearing Capacity Value of the Shallow Foundation Permit from the qc Data was obtained at No. Test. S - 1, with a depth of 5 meters, the permitted bearing capacity (Qi) was 3.8 (Ton / m2) with a square foundation width B = 1 m and No. Test. S – 2, with a depth of 5 meters, the permissible bearing capacity (Qi) is 4.53 (Ton/m2) B = 1 m